A Single Copy of the Recently Identified Dual Oxidase Maturation Factor (DUOXA) 1 Gene Produces Only Mild Transient Hypothyroidism in a Patient with a Novel Biallelic DUOXA2 Mutation and Monoallelic DUOXA1 Deletion - Hulur, Imge (Endocrine Society, 2011)
CONTEXT: Dual oxidases (DUOX1 and DUOX2) play a crucial role in the generation of hydrogen peroxide required in the oxidation of iodide and the synthesis of thyroid hormone. Heterodimerization with specific maturation factors (DUOXA1 and DUOXA2) is essential for the maturation and function of the DUOX enzyme complexes. Biallelic loss-of-function mutations of DUOX2 result in congenital hypothyroidism (CH), whereas a single reported case of homozygous DUOXA2 mutation (Y246X) has been associated with mild CH. OBJECTIVE: We now report an infant with transient CH due to a complex genetic alteration of the DUOX/DUOXA system. RESULTS: Our patient was born to euthyroid nonconsanguineous parents and presented with an elevated TSH and enlarged thyroid gland at neonatal screening. Genetic analysis revealed a missense mutation (C189R) on the maternal DUOXA2 allele. The mutant DUOXA2 protein showed complete loss-of-function in reconstituting DUOX2 in vitro. The apparent C189R homozygosity of the proband in the absence of the same mutation in the father led to detailed gene mapping, revealing an approximately 43-kb pair deletion encompassing DUOX2, DUOXA1, and DUOXA2. Thus, in addition to being deficient in DUOXA2, the proband lacks one allele of DUOX2 and DUOXA1 but has two functioning DUOX1 alleles. CONCLUSION: The transient CH in the presence of only one functional maturation factor allele indicates a high level of functional redundancy in the DUOX/DUOXA system.